The Determinant of Tax Litigation: Analysis Based on Resource-Based View Theory - Naniek Noviari; I Gusti Ayu Eka Damayanthi; Luh Gede Krisna Dewi (Jurnal Ilmiah Akuntansi, 2025)
Despite the growing frequency, high costs, and substantial loss risk of tax litigation cases in Indonesia under the self-assessment system, empirical evidence remains limited and inconclusive regarding whether firms’ political connections improve tax litigation outcomes. This research examines the determinant of tax litigation. A saturated sampling technique was applied to obtain 292 observations of non-financial sector companies listed on the Indonesia Stock Exchange that have tax litigation cases during 2014-2019. Panel data regression analysis was conducted using e-views 12 software. This research verify that political connections have no influence on tax litigation. This study provide insights into the determinant of tax litigation within the resource-based view (RBV) theory framework. The practical benefits of this research is management should consider that political connections is not a competitive advantage internal resource regarding tax litigation case. The limitations of this study are the enggament with tax consultants and the type of tax litigation not be discussed due to data lacknes. Further research could incorporate tax consultant’s engagement as an independent variable and separate the type of tax litigation as dependent variables.